Automatic external defibrillator (AED) location - seconds that save lifes - Wojciech Timler; Filip Jaskiewicz; Joanna Kempa; Dariusz Timler (BMC, 2024)
Abstract Introduction and objective Sudden cardiac arrest (SCA) is a significant cause of adult mortality, categorized into in-hospital (IHCA) and out-of-hospital (OHCA). Survival in OHCA depends on early diagnosis, alerting Emergency Medical Service (EMS), high-quality bystander resuscitation, and prompt Automatic External Defibrillator (AED) use. Accelerating technological progress supports faster AED retrieval and use, but there are barriers in real-life OHCA situations. The study assesses 6th-year medical students' ability to locate AEDs using smartphones, revealing challenges and proposing solutions. Material & Methods The study was conducted in 2022-2023 at the Medical University of Lodz, Poland. Respondents completed a survey on AED knowledge and characteristics, followed by a task to find the nearest AED using their own smartphones. As common sources did not list the University AEDs, respondents were instructed to locate the nearest AED outside the research site. Results A total of 300 6th-year medical students took part in the study. Only 3.3% had an AED locating app. Only 32% of students claimed to know where the AED nearest to their home is. All 300 had received AED training, and almost half had been witness to a resuscitation. Out of the 291 medical students who completed the AED location task, the median time to locate the nearest AED was 58 s. Most participants (86.6%) found the AED within 100 s, and over half (53%) did so in under 1 min. Conclusions National registration of AEDs should be mandatory. A unified source of all AEDs mapped should be created or added to existing ones. With a median of under one minute, searching for AED by a bystander should be considered as a point in the chain of survival.